Silent infarction in sickle cell disease is associated with brain volume loss in excess of infarct volume - Jones, R. Sky; Donahue, Manus J.; Davis, L. Taylor; Pruthi, Sumit; Waddle, Spencer L.; Custer, Chelsea; Patel, Niral J.; DeBaun, Michael R.; Kassim, Adetola A.; Rodeghier, Mark; Jordan, Lori C. (Frontiers in Neurology, 2023)
Introduction Sickle cell disease (SCD) increases cerebral infarct risk, but reported effects on brain volume have varied. More detailed information using larger cohorts and contemporary methods could motivate the use of longitudinal brain volume assessment in SCD as an automated marker of disease stability or future progression. The purpose of this study was to rigorously evaluate whether children and young adults with SCD have reduced gray matter volume (GMV) and white matter volume (WMV) compared to healthy controls using high-resolution MRI. We tested the hypotheses that (i) elevated CBF, a marker of cerebral hemodynamic compensation in SCD, is associated with global and regional brain atrophy, and (ii) silent cerebral infarct burden is associated with brain atrophy in excess of infarct volume. Methods Healthy controls (n = 49) and SCD participants without overt stroke (n = 88) aged 7–32 years completed 3 T brain MRI; pseudocontinuous arterial spin labeling measured CBF. Multivariable linear regressions assessed associations of independent variables with GMV, WMV, and volumes of cortical/subcortical regions. Results Reduced hemoglobin was associated with reductions in both GMV (p = 0.032) and WMV (p = 0.005); reduced arterial oxygen content (CaO2) was also associated with reductions in GMV (p = 0.035) and WMV (p = 0.006). Elevated gray matter CBF was associated with reduced WMV (p = 0.018). Infarct burden was associated with reductions in WMV 30-fold greater than the infarct volume itself (p = 0.005). Increased GM CBF correlated with volumetric reductions of the insula and left and right caudate nuclei (p = 0.017, 0.017, 0.036, respectively). Infarct burden was associated with reduced left and right nucleus accumbens, right thalamus, and anterior corpus callosum volumes (p = 0.002, 0.002, 0.009, 0.002, respectively). Discussion We demonstrate that anemia and decreased CaO2 are associated with reductions in GMV and WMV in SCD. Increased CBF and infarct burden were also associated with reduced volume in subcortical structures. Global WMV deficits associated with infarct burden far exceed infarct volume itself. Hemodynamic compensation via increased cerebral blood flow in SCD seems inadequate to prevent brain volume loss. Our work highlights that silent cerebral infarcts are just a portion of the brain injury that occurs in SCD; brain volume is another potential biomarker of brain injury in SCD.